Three new species and one new record of Ampulex Jurine (Hymenoptera, Ampulicidae) from China, with a key to Chinese species - Zhi-Zhi Liu; Qiang Li; Li Ma (Journal of Hymenoptera Research)
The taxonomy of the genus Ampulex in China is studied, three new species from Yunnan, Fujian, Guangdong, and Guangxi Provinces are described: Ampulex fronticarinalis Liu & Li, sp. nov., Ampulex genapunctata Liu & Li, sp. nov., and Ampulex rubifemoralis Liu & Li, sp. nov. Additionally, Ampulex tridentata Tsuneki, 1982 is recorded from China, and the female of Ampulex clypecomplana Chen and Q. Li, 2010 is described for the first time. An identification key and a checklist of the Chinese species of Ampulex are provided.